2008
DOI: 10.1016/j.vaccine.2008.01.026
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of an immunochemotherapeutic protocol constituted of N-methyl meglumine antimoniate (Glucantime®) and the recombinant Leish-110f®+MPL-SE® vaccine to treat canine visceral leishmaniasis

Abstract: The evaluation of the efficacy of an immunochemotherapy protocol to treat symptomatic dogs naturally infected with Leishmania chagasi was studied. This clinical trial had the purpose to test the combination of N-methyl meglumine antimoniate (Glucantime and the second generation recombinant vaccine Leish-110f plus the adjuvant MPL-SE to treat the canine leishmaniasis (CanL). Thirty symptomatic naturally infected mongrel dogs were divided into five groups. Animals received standard treatment with Glucantime or t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
49
0
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
4
3
3

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(52 citation statements)
references
References 48 publications
2
49
0
1
Order By: Relevance
“…The gp63?Hsp70?MPL-A vaccine significantly protected the BALB/c mice against L. donovani infection and reduced the parasite load in liver by 97.13 % and in spleen by 94.35 %. The results are in consistence with previous studies which showed that addition of monophosphoryl lipid plus squalene emulsion (MPL-SE) to a cocktail vaccine (containing H1, HASPB1 and MML) or Leish-110f conferred partial or significant protection in dogs against VL respectively (Moreno et al 2007;Miret et al 2008). Experimental infection of immunized mice and hamsters have demonstrated that Leish-111f?MPL-SE induced significant protection against L. infantum infection, with reduction in parasite loads up to 99.6 % (Coler et al 2007).…”
Section: Discussionsupporting
confidence: 89%
“…The gp63?Hsp70?MPL-A vaccine significantly protected the BALB/c mice against L. donovani infection and reduced the parasite load in liver by 97.13 % and in spleen by 94.35 %. The results are in consistence with previous studies which showed that addition of monophosphoryl lipid plus squalene emulsion (MPL-SE) to a cocktail vaccine (containing H1, HASPB1 and MML) or Leish-110f conferred partial or significant protection in dogs against VL respectively (Moreno et al 2007;Miret et al 2008). Experimental infection of immunized mice and hamsters have demonstrated that Leish-111f?MPL-SE induced significant protection against L. infantum infection, with reduction in parasite loads up to 99.6 % (Coler et al 2007).…”
Section: Discussionsupporting
confidence: 89%
“…The primary objective of the present study was to develop a subunit vaccine against VL with high efficacy and broad coverage of human or animal populations. Although Leish-111f/L110, our first-generation polyprotein vaccine antigens, are promising, i.e., they are protective against both CL and VL in mouse models (9,11), show therapeutic vaccine efficacy for canine VL (26,45), and are showing some promise in human clinical trials (25,31), the vaccine failed to protect dogs from VL in a field trial (18), and it may be possible to obtain a new construct with improved efficacy. KSAC could be one such antigen, because it consistently protected against L. infantum infection as well as or better than Leish-111f/L110, as shown in this study, and also protected against L. major infection better than L110f using a sandfly challenge model (R. Gomes, C. Teixeira, F. Oliveira, P. G. Lawyer, D.-E. Elnaiem, Y. Goto, A. Bhatia, S. Bertholet, R. N. Coler, R. F. Howard, S. G. Reed, S. Kamhawi, and J. G. Valenzuela, unpublished data).…”
Section: Discussionmentioning
confidence: 99%
“…The mixture of recombinant components of Leish-111f was highly immunogenic in dogs [253] but failed to protect them against L. infantum infection and did not prevent disease development in a phase III trial in dogs [114,254]. Recently, when Leish-110f-MPL-SE was co-administered with Glucantime in dogs, the number of deaths was reduced, there was higher survival probability and specific cellular reactivity upon immunization was observed in comparison to dogs who received Glucantime only [255].…”
Section: Leish-111fmentioning
confidence: 99%